Caracterización del desarollo de la sexualidad como dimensión fundamental de la personalidad y transversalidad curricular en las diferenetes áreas de estudio, aplicada a los estudiantes de séptimo año de educación básica de la escuela Miguel Heredia Crespo del cantón Ponce Enríquez periodo lectivo 2010-2011 - García Murillo, Flor Esperanza (2013)
To achieve this goal, research techniques such as the survey and the field observation were applied, because it was possible to determine that there are serious limitations in the study of sexuality, which has repercussions on habitual forms of behavior. It is time to apply a methodology that promotes curricular transversality, depending on the form of the students' personality from the sexual education.